Pengaruh Pengetahuan Keuangan, Gaya Hidup, Media Sosial dan Kecerdasan Emosional terhadap Perilaku Keuangan (Studi pada Tenaga Kesehatan yang Menangani Covid-19 di Buleleng): Studi pada Tenaga Kesehatan yang Menangani Covid-19 di Buleleng - Marheni, Ni Kadek Lely; Herawati, Nyoman Trisna (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of financial knowledge, lifestyle, social media and emotional intelligence on the financial behavior of Health Workers who handle Covid-19 in Buleleng. The research method used is a quantitative method measured using a likert scale. Data was obtained by distributing online questionnaires using google form. The population in this study were Health Workers who handled Covid-19 in Buleleng. The sampling method was carried out by the purposive sampling method, in order to obtain a total sample of 350 respondents. The research data was processed using descriptive statistical tests, data quality tests, classical assumption tests, and hypothesis testing with the help of IBM SPSS Statistic 23 software. The results of this study stated that the variables of financial knowledge (X1), social media (X3), emotional intelligence (X4) has a positive and significant effect on the financial behavior of Health Workers who handle Covid-19 in Buleleng. Meanwhile, lifestyle (X2) has a negative and significant effect